Fatal Haemophilus influenzae type a sepsis in an infant. Issue 3 (18th December 2012) - Francis, Joshua; Anders, Marc; Lobegeier, Pam; Nourse, Clare
Abstract : Abstract: Haemophilus influenzae type a can cause severe sepsis, as demonstrated by the case described. Epidemiology of sepsis in childhood is changing. Regardless of the pathogen involved, management of children with septic shock involves resuscitative measures and empiric antibiotics. The following case of H. influenzae type a sepsis proved fatal in spite of appropriate therapy.